Energy, Exergy, and Economic Performances of Combined CO2 Power and Cooling Systems: Comparison and Multi-Objective Optimization - Yu, Aofang; Xing, Lingli; Lin, Xinxing; Ou, Shaoduan (Frontiers in Energy Research, 2022)
As a nature working fluid, carbon dioxide (CO2) has been extensively applied to produce power and cooling in thermodynamic cycles. So far, various combined CO2 power and cooling systems have been proposed to enhance the energy conversion efficiency and reduce the cost further. However, how to evaluate the performance of different combined systems for a practical application scenario is still an open question. Thus, in this work, four representative systems are considered to investigate and compare the energy, exergy and economic performances under design conditions. The corresponding models are established and various performance parameters are calculated. According to the obtained results, the total products of four systems are 6831.36kW, 4421.73kW, 6252.81kW and 6978.69kW, respectively. The minimum total cost is obtained by System 2. Thereafter, in order to maximize the total product (the sum of net work and refrigerating capacity), and simultaneously minimize the total cost, key system parameters are optimized by a multi-objective optimization algorithm, namely NSGA-Ⅱ. The optimization results show that System 1 provides the highest total product (7345.4kW), while System 2 has the lowest cost (27.51/h). After comprehensive comparisons for the net work, cooling capacity, efficiencies and total cost, System 1 is thought as the best among the considered four systems.